Tobac-no! A Grade Six Smoking Prevention Curriculum Unit - McKinty, Marie Christine (My University, 1994)
Smoking is still the leading cause of death and illness in Canada today (Wong, 1990). The process of addiction begins for many as early as 12 years of age (Health Canada, Canadian Association for School Health, Canadian Council on Smoking and Health, Heart and Stroke Foundation, 1991), and currently, only 3% of people ever begin smoking beyond their teens. King and Coles (1992) established that by age 15,22% of males and 29% of females are occasional or regular smokers. These and other statistics clearly establish that smoking is a major health care concern. In order to effectively reduce or eliminate this problem, the root causes or determinants of smoking behaviour must first be recognized. The various demographic, socioeconomic, personality and biologic factors (Flay, d'Avernas, Best, Kersell & Ryan, 1983) must be addressed by comprehensive strategies which include the goals of promotion, prevention, intervention and support. These goals should be achieved by means of appropriate instruction, social support, support services and physical environmental intervention (Council for a Tobacco-Free Ontario [CTFO], 1991; Garcia, d'Avernas & Best, 1988).
The focus of this paper is instruction, which is defined to include a well developed curriculum, relevant teaching and learning materials and appropriate teacher preparation. The principles of a Social Influences Approach are applied to the development of TOBAC-NO!, a grade six smoking prevention curriculum unit for the Hamilton Board of Education.
Keywords: Teacher Education and Professional Development; Teacher Education and Professional Development